2021
DOI: 10.48550/arxiv.2103.07467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Singlet-assisted electroweak phase transition at two loops

Lauri Niemi,
Philipp Schicho,
Tuomas V. I. Tenkanen

Abstract: We investigate the electroweak phase transition in the real-singlet extension of the Standard Model at two-loop level, building upon existing one-loop studies. We calculate the effective potential in the high-temperature approximation and detail the required resummations at two-loop order. In typical strong-transition scenarios, we find deviations of order 20% − 50% from one-loop results in transition strength and critical temperature for both one-and two-step phase transitions. For extremely strong transition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 64 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…6 and its Z 2 -symmetric version. Most studies of this system are based on perturbative calculations, while only very recently first non-perturbative analyses have appeared [308], [309], [342] showing significant limitations of the perturbative approach. This subject is also interesting in the context of gravitational wave detection [343].…”
Section: Other Cosmological Implications Of the Higgs Portalmentioning
confidence: 99%
“…6 and its Z 2 -symmetric version. Most studies of this system are based on perturbative calculations, while only very recently first non-perturbative analyses have appeared [308], [309], [342] showing significant limitations of the perturbative approach. This subject is also interesting in the context of gravitational wave detection [343].…”
Section: Other Cosmological Implications Of the Higgs Portalmentioning
confidence: 99%
“…To improve convergence, and avoid large logarithms, it is useful to work with a dimensionally reduced theory in three dimensions. All temperature dependence is here contained in effective couplings [2][3][4]43,44,61,62]. Quantities like the latent heat, speed of sound, entropy density, and heat capacity are straightforward to calculate in the effective-field-theory framework.…”
Section: Phase Transitions and Perturbative Methodsmentioning
confidence: 99%
“…Gravitational waves offer a new way to study primordial phase transitions. And the area is increasingly active [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] after the discovery of gravitational waves by the LIGO collaboration [21]. As such, much work is spent looking at the Electroweak phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we truncate the perturbative expansion, keeping only the one-loop order terms, which imposes the dependence on the renormalization scale. The two-loop analysis of EWPT in a singlet-extended SM performed recently [49] has revealed that the two-loop corrections may change the values of the critical temperature and the latent heat by 20-50% (up to 100%) depending on the model. In respect to these issues, we refer to the recent review [50] for an extensive discussion of various theoretical uncertainties typical in investigations of the cosmological first order phase transitions.…”
Section: Effective Potential Of the Modelmentioning
confidence: 99%